Understanding the passivation behavior and film chemistry of four corrosion-resistant alloys in the simulated flue gas condensates. (June 2022) - Wang, Mingtao; Wang, Liwei; Zhao, Kang; Liu, Yuxi; Cui, Zhongyu
Abstract: The passivation behavior and passive film composition of 254SMO, 316 L, 310 S stainless steels, and C276 nickel-based alloy in simulated desulfurization flue gas condensates at 60 °C were studied. The four alloys exhibited similar passivation behavior and capacitive properties in simulated flue gas condensate at 60 °C. Mott-Schottky analysis is performed to obtain semiconductor properties such as semiconductor type, carrier density, flat-band potential of the passive film. Electrochemical experiments show that four alloys form protective passive films in simulated flue gas condensate, among which 310 S has the best corrosion resistance, while C276 has the worst corrosion resistance, and the other two stainless steels have similar corrosion resistance. The passive film of the three stainless steels is mainly composed of Cr and Fe. The film generated on 254SMO and 316 L have similar compositions, while that of C276 is mainly composed of Cr, Fe, Ni, and a small amount of Co and W. Compared with the passive film formed by natural immersion, the electrochemically formed passive film promotes the enrichment of Cr in 254SMO and 310 S and the enrichment of Fe in C276. Graphical Abstract: ga1